Vitamin D Deficiency as a Risk Factor of Breast Cancer - Irmaghana Basharat, Naeem Zia , Faisal Murad, Asif Zafar Malik, Nadir Mahmood (Journal of Rawalpindi Medical College, 2014)
Background: To determine the frequency of Vitamin D insufficiency in patients with breast cancer. Methods: In this comparative study diagnosed cases of carcinoma breast (n=50) were enrolled. Equal number were taken as control. Patients undergoing current dialysis treatment, elevated liver enzymes, primary hyperparathyroidism, hypercalcemia, hypercalciuria, or Paget’s disease and already taking therapy to improve vitamin D levels were excluded. Vitamin D levels were measured by Enzyme Linked Immunosorbant Assay(ELISA).Chi square test was applied to compare the vitamin D deficiency in cases and controls. Odds ratio were calculated. Stratification was done for duration of disease (in months) age of patients, family history to control the effect modifier. Results: In our study, 64%(n=32) in cases and 100%(n=50) in controls were between 25-45 years of age while 36%(n=18) in cases group were between 46-65 years of age, Mean+SD was calculated as 40.60+10.02 and 32.08+4.12 respectively.Frequency of vitamin D deficiency was 92% in cases and 63% in controls. Conclusion: Fequency of Vitamin D insufficiency in patients with breast cancer was significantly higher as compared to the controls. Dietary vitamin D and casual sunlight exposure may be among the modifiable risk factors for breast cancer.